2012
DOI: 10.1016/j.jacc.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rs5065 Atrial Natriuretic Peptide Gene Variant on Coronary Artery Disease

Abstract: The MA of rs5065 ANP gene variant associates with increased susceptibility to ACS and has unfavorable prognostic value in CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…This variant resembles ANP molecules in other mammalian sepiecs such as porcine, rat and mouse, which all contain two Arg residues at the C-terminus (Koller and Goeddel, 1992). The minor C allele was associated with high risks of hypertension (Niu, 2011), stroke (Rubattu et al, 2004), coronary artery disease (Barbato et al, 2012a), and myocardial infarction (Cannone et al, 2013b). In other studies, however, such an association was not confirmed (Kato et al, 2002; Lynch et al, 2008).…”
Section: Nppa Variants In Cardiovascular Diseasementioning
confidence: 99%
“…This variant resembles ANP molecules in other mammalian sepiecs such as porcine, rat and mouse, which all contain two Arg residues at the C-terminus (Koller and Goeddel, 1992). The minor C allele was associated with high risks of hypertension (Niu, 2011), stroke (Rubattu et al, 2004), coronary artery disease (Barbato et al, 2012a), and myocardial infarction (Cannone et al, 2013b). In other studies, however, such an association was not confirmed (Kato et al, 2002; Lynch et al, 2008).…”
Section: Nppa Variants In Cardiovascular Diseasementioning
confidence: 99%
“…Some researchers found that the minor allele G was associated with higher risk of acute coronary syndrome [11] and greater severities of CAD [12], while other studies reported that the major allele A was more prevalent in CAD patients [13] and was associated with a higher risk of hypertension, more adverse ventricular remodeling and a higher rate of hospital readmission [7]. The discrepancy could be explained by diverse patient populations and different outcomes defining CAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our current meta-analysis, the inter-gene and gene-environment interactions could not be conducted owing to the data deficiency. Last but not the least, genetic epidemiological studies show different genetic variants can predispose to different subtypes of CHD [4042]. So subtypes of CHD, such as myocardial infarction, acute coronary syndrome and stable angina should be further analyzed.…”
Section: Discussionmentioning
confidence: 99%